MUD enabled deep learning framework for anomaly detection in IoT integrated smart building - S, Mirdula; M, Roopa (e-Prime, 2023)
•Using Machine learning model to classify the MUD profiles.•Providing security against various device level attacks like DDoS and BoTNet.•Using the classified MUD policies to train the deep learning Model.•Implementing the deep learning based prediction model in a IoT based smart building environment.•Real-time implementation and discussion of results in detail. Nowadays, many Internet of Things (IoT) devices of different types are used in creating smart applications like smart cities, smart industries, smart environments, and the applications of industry-4.0. IoT devices are used for different purposes, such as security, remote monitoring, resource allocation, threats, ecosystems, and vulnerabilities. This paper proposed a deep learning algorithm-based solution to tighten the security level in the IoT-Smart environment network. The Intrusion Detection System (IDS) considered in this paper is Network IDS, which investigates the manufacturer usage description, digital twins, and deep learning-based user behavior information. IoT devices' communication and the users in smart buildings are automatically connected in the Intelligent Communication system. Since many devices and users are interconnected in smart buildings, the probability of cyber-attack is high. Thus, better security is needed in smart buildings and smart environments. It should focus on securing IoT devices, users, and their communication. Hence, this paper developed a deep learning-based anomaly detection framework to dynamically monitor the issues and problems with MUD profiles and detect the anomaly behavior. The Manufacturer Usage Description (MUD) profiles, dynamic user behavior, IoT devices' traffic data the pattern of abnormal/anomaly traffic at the device level is predicted while traffic occurs. The MUD-ML-based model is implemented in Python software, verifying the results.